2009
DOI: 10.1124/jpet.109.152181
|View full text |Cite
|
Sign up to set email alerts
|

HSP70 Confers Protection against Indomethacin-Induced Lesions of the Small Intestine

Abstract: In line with improvements in diagnostic procedures to detect intestinal lesions, it has become clear that nonsteroidal antiinflammatory drugs (NSAIDs) such as indomethacin induce lesions not only in the stomach but also in the small intestine. However, clinical protocols for the treatment of NSAID-induced lesions of the small intestine have not been established. It is known that heat shock proteins (HSPs), particularly HSP70, confer protection against various stressors, and more recently, the anti-inflammatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 41 publications
(38 reference statements)
0
34
0
Order By: Relevance
“…On the other hand, TNF-α is the prototypical member of a family of cytokines that also include the Fas, CD40 and TNF-related apoptosis inducing ligands, and that induce apoptosis, differentiation, cell activation, and inflammation (29). Indomethacin-induced epithelial cell apoptosis in vivo was also reported by Takada et al (30) and Asano et al (31). These authors confirmed that apoptotic cell death occurred in the small intestine treated with indomethacin based on an evaluation of caspases-3/7 activity and a TuNeL assay.…”
Section: Discussionmentioning
confidence: 95%
“…On the other hand, TNF-α is the prototypical member of a family of cytokines that also include the Fas, CD40 and TNF-related apoptosis inducing ligands, and that induce apoptosis, differentiation, cell activation, and inflammation (29). Indomethacin-induced epithelial cell apoptosis in vivo was also reported by Takada et al (30) and Asano et al (31). These authors confirmed that apoptotic cell death occurred in the small intestine treated with indomethacin based on an evaluation of caspases-3/7 activity and a TuNeL assay.…”
Section: Discussionmentioning
confidence: 95%
“…As outlined in Introduction, the beneficial effects of HSP70 in animal models of various diseases suggest the potential therapeutic benefit of HSP70 inducers for these conditions (Tanaka et al, 2007Asano et al, 2009;Suemasu et al, 2009;Yamashita et al, 2010), a possibility that can now be expanded to include AD based on the results of the present study. A number of recent studies have revealed new molecules that induce HSPs (Kieran et al, 2004;Westerheide et al, 2004;Yan et al, 2004).…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, GGA, a leading anti-ulcer drug on the Japanese market, has been reported to be an HSP inducer, up-regulating various HSPs not only in cultured gastric mucosal cells but also in various tissues in vivo (41). It was reported that GGA suppresses not only gastric lesions but also lesions of the small intestine, inflammatory bowel disease-related experimental colitis, and neurodegenerative diseases (39,40,46,47). On the other hand, the use of HSP70 inducers in cosmetics -1) (B).…”
Section: Discussionmentioning
confidence: 99%